RNA‐Seq Analysis of Allele‐Specific Expression in the Mouse Cochlea. (2nd September 2014) - Ho, Maria K. L.; Hasin, Yehudit; Lusis, Aldons J.; Friedman, Rick A.
Abstract : Objectives: Age‐related hearing impairment or presbycusis is one of the most common sensory abnormalities in the world. Mouse models have been widely used in studies of hearing loss to separate genetic and environmental influences. We will describe novel cis‐ and trans‐regulation and dominance patterns in gene expression levels from cochlea of mice. Methods: Next‐generation sequencing (RNA‐Seq) data has been acquired from cochlea of three F1 mouse hybrid strains (n = 4) from parental strains C57BL/6J, DBA/2J, C3H/HeJ. Results: An analysis of allele‐specific expression will be reported and novel transcripts, isoforms, cis and trans‐regulation, long non‐coding RNAs, and dominance patterns will be discussed in relation to known genes. Conclusions: This will help to elucidate mechanisms and better understand the genetic backdrop of age related hearing impairment.